Hubungan Beban Dan Lendutan Terhadap Balok Beton Bertulang Berongga - Razak, Rismawati; Sariman, Syahrul; Yuniarto, Eka (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
When a beam structure is loaded, it is held in compression by concrete while the tension area is fully carried by reinforcing steel, so that the concrete cross-section in the tension section below the neutral line is not considered to be carrying the load. So in the concrete tension area filled with plastic bottles, in order to obtain a lighter structure, reduce the volume of concrete/cement and reduce environmental pollution. In this study used reinforced concrete beams with dimensions of 175 x 350 x 3200 mm. The test object consists of 3 (three) namely 1 normal beam and 2 hollow beams with the same length, namely 2640 mm and differentiated according to height, namely 120 mm (2 layers of bottles)-BR2 and 180 mm (3 layers of bottles)-BR3. The test results show that the load-deflection relationship is relatively the same. This shows that the voids in the pure bending moment area provide relatively the same stiffness as the normal beam stiffness. The crack patterns for all test results show that normal and hollow beams experience flexural failure.